The UV-Vis Study On Anthocyanin Pigments Activities Extracted From Gayo Arabika Coffee Husks - Hasby Hasby; Nurhafidhah Nurhafidhah; Said Ali Akbar (Elkawnie: Journal of Islamic Science and Technology, 2019)
The anthocyanin activity of Gayo Arabica coffee husk in variations in acid solution, temperature, and pH has been assessed through UV-Vis studies. It is important to optimize these factors to increase the long-term stability of anthocyanins for use in various fields. Gayo Arabica coffee husks was extracted through maceration method with methanol. This process obtained a coffee husks extract of 1.176 mg/μL. The UV-Vis spectrum of the extract displayed the major absorption peak at λmax= 529 nm in hydrochloric acid (HCl), this assigned by the electronic transition from flavylium as the particular characteristic of anthocyanin compounds. The anthocyanin from the extract was stable at temperatures of 35oC and 50oC, to have a major absorption peak at λmax= 529 nm. Therefore, it could probably be said that the lower the temperature, the higher the absorbance value of anthocyanin. Then, husks extract was getting red at pH 1 and 3; almost colorless at pH 5, 8 and 10; and yellow at pH 12. The more acidic conditions causes more anthocyanin pigments to be observed in the form of flavylium or oxonium cations color. Finally, Gayo Arabica coffee husks extract can absorb both ultraviolet (UV) and visible light (visible).